PEMBINAAN AKHLAKUL KARIMAH SANTRI KELAS I MELALUI PEMBELAJARAN KITAB AL-AKHLAK LIL BANIN DI PONDOK PESANTREN ASHHABUL YAMIN LASI TUO - Windy Divaci Anastasya; Arman Husni; Yelfi Dewi; Salmi Wati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research explores the challenges faced by Pondok Pesantren Ashhabul Yamin Lasi in fostering noble character among students through the teaching of Al-Akhlak Lil Banin. Despite the book’s emphasis on moral and ethical values, issues such as a lack of respect for teachers, rule violations, inappropriate student behavior, incidents of theft, and improper scribbles in textbooks remain prevalent. These challenges indicate that the expected character development outcomes have not been fully achieved. The study aims to assess the effectiveness of akhlaq al-karimah cultivation through Al-Akhlak Lil Banin Juz I and examine the teaching methods implemented. Using a qualitative descriptive approach, data were gathered through interviews, observations, and documentation. The key informants in this study included teachers of Al-Akhlak Lil Banin as the primary sources, while the head of the madrasah and first-year students served as supporting informants. The data analysis process involved reduction, presentation, and verification, with validity ensured through triangulation and rigorous observation. The findings indicate that character formation at the pesantren is guided by a value-based approach, incorporating methods such as habituation, role modeling, storytelling, advice, question-and-answer sessions, and discussions. Meanwhile, the instructional methods for Al-Akhlak Lil Banin Juz I include the bandongan method, discussions, and storytelling. These results suggest that while structured teaching methods are in place, further innovation in instructional strategies is necessary to ensure that akhlaq al-karimah values are deeply instilled in students' daily lives.